Assessment and Accountability in Education in Ontario - Earl, Lorna (Canadian Journal of Education/Revue canadienne de l'éducation, 1995)
In recent years, Ontario has joined many other provinces in grappling with the issues of assessment and accountability. Although Ontario does not have a long-standing history of standardized assessment or testing, a ferment of activity has occurred since the mid-1980s. This activity has included a number of program reviews (in different subjects areas, using sampling techniques), a literacy assessment in grade 9, and examination reviews in the final secondary year. The next few years will be important ones as Ontario tries to juggle the critical issues associated with changing social, economic, and political conditions; with the role of teachers in assessment; with the complexity and difficulty of communicating with a widely varied audience; and with interpreting and using assessment results wisely. Au cours des dernières années, l’Ontario s’est penché, à l’instar de nombreuses autres provinces, sur les questions d’évaluation et de responsabilité. Bien que l’Ontario n’ait pas une longue tradition en matière d’évaluation ou de tests standardisés, des activités en ce sens ont commencé à surgir depuis le début des années 80. Elles comprennent bon nombre d’analyses de programmes (dans différentes matières, à l’aide de techniques d’échantillonnage), l’évaluation des capacités de lecture et d’écriture en 9e année et des analyses des résultats d’examen à la fin du secondaire. Les années qui viennent seront importantes puisque l’Ontario tentera de faire face aux questions essentielles associées à l’évolution des conditions sociales, économiques et politiques, au rôle des enseignants dans l’évaluation, à la complexité et à la difficulté de communiquer avec un auditoire très varié et à l’interprétation et à l’utilisation judicieuses des résultats des évaluations.